2020
DOI: 10.1123/jsr.2019-0348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Abdominal Electrical Muscle Stimulation Training With and Without Superimposed Voluntary Muscular Contraction on Lumbopelvic Control

Abstract: Context: Electrical muscle stimulation (EMS) was designed for artificial muscle activation or superimposed training. Objectives: To compare the effects of 8 weeks of superimposed technique (ST; application of electrical stimulation during a voluntary muscle action) and EMS on the cross-sectional area of the rectus abdominis, lateral abdominal wall, and on lumbopelvic control. Setting: University research laboratory. Design: Randomized controlled trial. Participants: Fifty healthy subjects were recruited and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…PFM training was shown to be bene cial for improving PFM strength, endurance, and LBPP at both the end of treatment and at the 3-month follow-up [13]. Although we con rmed that abdominal electrical stimulation could improve lumbopelvic control [14], there have been no reports demonstrating that PFM training directly affects lumbopelvic control based on functional tests. Although the cause and effect relationship between lumbopelvic stability and LBPP is unclear, improved lumbopelvic control function will likely promote prevention of, and recovery from, LBPP in women with SUI.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…PFM training was shown to be bene cial for improving PFM strength, endurance, and LBPP at both the end of treatment and at the 3-month follow-up [13]. Although we con rmed that abdominal electrical stimulation could improve lumbopelvic control [14], there have been no reports demonstrating that PFM training directly affects lumbopelvic control based on functional tests. Although the cause and effect relationship between lumbopelvic stability and LBPP is unclear, improved lumbopelvic control function will likely promote prevention of, and recovery from, LBPP in women with SUI.…”
Section: Introductionmentioning
confidence: 59%
“…Lumbopelvic control and stability was contributed to core muscles, such as deep abdominal muscle and PFM [18,19]. After, we demonstrated that abdominal electrical stimulation could improve lumbopelvic control [14], we wondered if the PFM training by ES would affect lumbopelvic control. Prior to carrying out the present study, a study was needed to con rm whether the PFM training by ES improved the PFM functions [15].…”
Section: Introductionmentioning
confidence: 99%
“…The one-and double-leg lowering tests were used to measure the subject's lumbopelvic control during movement of the lower limbs [9,14,[22][23][24]. In the supine position, the subject exed the hips and knees to 90°.…”
Section: Lumbopelvic Control: One-and Double-leg Lowering Testsmentioning
confidence: 99%
“…In the supine position, the subject exed the hips and knees to 90°. A Smart KEMA pressure sensor (KOREATECH Co., Ltd., Seoul, Korea) was set to 40 mmHg and placed below the lordotic curvature of the spine between L1 and S1, with the hips and knees in 90° of exion (Figure 2) [14,24]. Using its strap, the Smart KEMA motion sensor (KOREATECH Co., Ltd.) was attached to the thigh between the greater trochanter and knee joint.…”
Section: Lumbopelvic Control: One-and Double-leg Lowering Testsmentioning
confidence: 99%
See 1 more Smart Citation